Clinical outcomes following discontinuation of metformin in patients with type 2 diabetes and advanced chronic kidney disease in Hong Kong: a territory-wide, retrospective cohort and target trial emulation studyResearch in context - Aimin Yang; Mai Shi; Hongjiang Wu; Eric SH. Lau; Johnny TK. Cheung; Xinge Zhang; Baoqi Fan; Tingting Chen; Alice PS. Kong; Andrea OY. Luk; Ronald CW. Ma; Juliana CN. Chan; et al. (EClinicalMedicine, 2024)
Summary: Background: Current labelling advises discontinuation of metformin when estimated glomerular filtration rate (eGFR) < 30 ml/min/1.73 m2 due to increased risk of lactic acidosis. However, in real-world practice, the risk-benefit ratios remain uncertain. We examined the risk associations of discontinued-metformin use with cardiorenal and clinical outcomes in patients with type 2 diabetes (T2D) and advanced chronic kidney disease. Methods: In this territory-wide, retrospective cohort and target trial emulation study, we included Chinese patients attending the Hong Kong Hospital Authority (HA) and enrolled in the Risk-Assessment-and-Management-Programme-for-Diabetes-Mellitus (RAMP-DM) from 2002 to 2019. Patients were stratified by discontinuation of metformin within six months after reaching eGFR < 30 ml/min/1.73 m2 from January 1, 2002 to December 31, 2018, and followed up until December 31 2019. We excluded patients who had observational time <6 months from eGFR < 30 ml/min/1.73 m2, and had their eGFR measured during a hospitalisation episode due to acute kidney injury, or missing diagnosis date of diabetes. We compared the risk associations of metformin discontinuation with clinical outcomes. The primary outcomes were major adverse cardiovascular events (MACE), end-stage kidney disease (ESKD), cancer, and all-cause mortality. A Cox-model with time-dependent exposure and covariates was used to estimate the hazard ratio (HR) of outcomes in a propensity-score overlap-weighted cohort. The risk of occurrence of lactic acidosis (serum lactate > 5.0 mmol/L with a concomitant blood pH < 7.35 or ICD-9 codes of 276.2) in discontinued-metformin versus continued-metformin users was assessed in a separate register-based cohort. Findings: A total of 33,586 metformin users with new-onset eGFR < 30 ml/min/1.73 m2 were included in the study, 7500 (22.3%) of whom discontinued metformin within 6 months whereas 26,086 (77.7%) continued use of metformin. During a median follow-up of 3.8 (IQR: 2.2–6.1) years, 16.4% (5505/33,586), 30.1% (10,113/33,586), and 7.1% (2171/30,682) had incident MACE, ESKD, and cancer respectively, and 44.4% (14,917/33,586) died. Compared to continued-metformin use, discontinuation was associated with higher risk of MACE (weighted and adjusted HR = 1.40, 95% CI: 1.29–1.52), ESKD (HR = 1.52, 1.42–1.62), and death (HR = 1.22, 1.18–1.27). No association was observed for cancer (HR = 0.93, 0.85–1.01). Discontinued-metformin users had higher change in HbA1c change at 6-month of follow-up versus continued-metformin users (weighted mean HbA1c level change: 0.5% [0.4–0.6%] versus 0.2% [0.1–0.2]). In the separate register-based cohort (n = 3235), null association was observed between metformin use and risk of lactic acidosis (weighted HR = 0.94 [0.53–1.64]). Interpretation: Our results suggest that discontinuation of metformin in patients with T2D and chronic kidney disease may be associated with increased risk of cardiovascular-renal events. Use of metformin below eGFR of 30 ml/min/1.73 m2 may be associated with cardiovascular, renal, and mortality benefits that need to be weighed against the risk of lactic acidosis, but further research is needed to validate these findings. Funding: CUHK Impact Research Fellowship Scheme.